Controllable room temperature phosphorescence, mechanoluminescence and polymorphism of a carbazole derivative. Issue 10 (1st September 2021) - Zhang, Hongyan; Ma, Huili; Huang, Wenbin; Gong, Wenqi; He, Zikai; Huang, Guangxi; Li, Bing Shi; Tang, Ben Zhong
Abstract : A carbazole derivative with room temperature phosphorescence, mechanoluminescence and polymorphism was designed and it was further utilized for preparing multicolored ML systems. The role of structure/packing on these novel properties was explored. Abstract : Room temperature phosphorescence (RTP) and mechanoluminescence (ML) materials are in high demand because of their promising applications in optoelectronic devices. However, most materials bear only one of these properties and molecules bearing both of them are rarely reported. Here, we report a carbazole derivative 1, which displays both RTP activity and near-ultraviolet ML properties. These properties are highly related to the packing modes and molecular configuration as revealed by the analysis of their crystal structures and theoretical calculations. The near-ultraviolet ML of 1 can further serve as the exciting light source to transfer its energy to luminescent dyes to realize colorful ML. The thermal-responsive RTP of 1 can be utilized to prepare anti-counterfeiting tags for simple security protection. This work has put forward a simple but efficient strategy to prepare multifunctional molecular systems bearing both RTP and ML properties.